Evaluation of Sulfate Resistance of Mortar Containing Palm Oil Fuel Ash from Different Sources - Bamaga, S.; Ismail, Mohamed; Majid, Z.; Ismail, M.; Hussin, M. (Springer, 2013)
In this study, laboratory tests were conducted to evaluate the sulfate resistance of three types of mortar containing palm oil fuel ash (POFA) collected from different palm oil mills. The compressive strength of three different concretes containing different types of POFA was also investigated. For comparison purpose plain Portland cement mortar and concrete were used as a reference. Ground POFA was used to partially replace Portland cement type I, 20 % by weight of binder. For testing the durability of mortar exposed to sulfate attack, the expansion of standard mortar bars immersed in 5 % sodium sulfate Na 2 SO 4 and magnesium sulfate MgSO 4 solutions for up to 15 weeks was determined. Moreover, FESEM micrograph and EDS analysis were carried out. The results of 28 days compressive strength of two concretes containing POFA showed higher compressive strength than that of plain Portland cement concrete. The expansion levels of blended mortars were in general lower than plain Portland cement mortar. The FESEM and EDS analysis showed good correlation to the results of expansion tests. © 2012 King Fahd University of Petroleum and Minerals.